Needs Assessment in Care of Adults With Anorectal Malformations and Exstrophy-Epispadias Complex in Germany - Ebert, Anne Karoline; Zwink, Nadine; Schwarzer, Nicole; Brunner, Lilian; Reutter, Heiko; Jenetzky, Ekkehart; Huber, Johannes; Ludwikowski, Barbara (Frontiers in Pediatrics, 2018)
Introduction Medical needs of adults with anorectal malformations (ARM) and the exstrophy-epispadias complex (EEC) are not fully understood. Therefore, the aim of the study was to evaluate how affected individuals get along with the current national medical care and what their medical or social long-term requirements are. Patients and methods Between 11/2014-07/2016 all adult members (≥ 18 years, ARM n=113, EEC n=126) of the German self-help organisations SoMA e.V. and Blasenekstrophie/Epispadie e.V. were contacted via email or post and asked to fill out an anonymous online questionnaire regarding medical requirements, treatment satisfaction, daily life impairment and expectations regarding physicians soft skills. The results were compared between both groups and male and female participants. Results 56 participants with ARM (median age 26 years, IQR 19-38) and 52 participants with EEC (median age 31 years, IQR 22-37) filled in the questionnaire completely. 45% of the ARM and 67% of the EEC participants contacted an urologist. A general surgeon was visited by 23% of the ARM individuals, a peadiatric surgeon by 20%. Although 60% of the females with ARM and 82% of the females with EEC assessed gynecological counselling as helpful or neutral, a small subgroup of ARM females (n=6, 16%; 70% non-isolated ARM or ARM with Hirschsprung disease and additional associated anomalies) were not satisfied. The majority of both groups reported no or only minor daily life impairment (p=0.38). Professional knowledge, paying attention to patients´ concerns, having empathy and taking enough time was important for over 90% of all participants. 38% of the ARM and 27% of the EEC individuals needed psychological support. Most medical consultations were judged to be helpful. Conclusion Although adults with ARM and EEC being a self-help organisation member and thus well informed and generally cope well, participants expressed their wish for expert counselling regarding family planning, reconstructive procedures, continence management, urological care and social welfare issues. Furthermore, specific expert consultations for gynecological issues in a subgroup of ARM females, mainly non-isolated, might be required. Actual needs of adults with rare conditions must be better clarified to improve medical care beyond childhood and adolescence.